Dynamic liquid–liquid–solid microextraction based on molecularly imprinted polymer filaments on-line coupling to high performance liquid chromatography for direct analysis of estrogens in complex samples - Zhong, Qisheng; Hu, Yufei; Hu, Yuling; Li, Gongke (Journal of Chromatography A, 2012)
► Dynamic liquid–liquid–solid microextraction (DLLSME) was originally developed. ► DLLSME based on molecularly imprinted polymeric filaments as solid acceptor phase. ► DLLSME on-line coupled to HPLC for direct analysis of trace estrogens. A novel sample preparation technique termed dynamic liquid–liquid–solid microextraction (DLLSME) was developed and on-line coupled to high performance liquid chromatography (HPLC) for direct extraction, desorption, and analysis of trace estrogens in complex samples. The DLLSME consists of the aqueous donor phase, the organic medium phase and the molecularly imprinted polymer filaments (MIPFs) as solid acceptor phase. The organic solvent with lesser density was directly added on top of the aqueous sample, and the dynamic extraction was performed by circulating the organic solvent through the MIPFs inserted into a PEEK tube which served as an extraction and desorption chamber. Afterwards, the extracted analytes on the MIPFs were on-line desorbed and then introduced into the HPLC for analysis. To evaluate the feasibility of the on-line system, a new DLLSME-HPLC method was developed for the analysis of five estrogens in aqueous samples by using 17β-estradiol MIPFs as the solid phase. Under the optimized conditions, the enrichment factors of 51–70, limits of detection of 0.08–0.25μg/L and precision within 4.5–6.9% were achieved. Furthermore, the proposed method was applied to the analysis of real samples including urine, milk and skin toner, satisfactory recovery (81.9–99.8%) and reproducibility (4.1–7.9%) were obtained. Especially, 0.59μg/L of 17β-estradiol was determined in female urine sample. The DLLSME offers an attractive alternative for direct analysis of trace analytes in aqueous samples and could potentially be extended to other adsorptive materials.